Serum pneumoproteins in tunnel construction workers - Ellingsen, Dag G.; Ulvestad, Bente; Bakke, Berit; Seljeflot, Ingebjørg; Barregard, Lars; Thomassen, Yngvar (International archives of occupational and environmental health, 2015)
Purpose The aim was to study inflammatory biomarkers in tunnel construction workers (TCW). Methods Surfactant protein D (SP-D), Clara cell protein 16 (CC-16) and C-reactive protein (CRP) were studied in serum of 90 TCW and 50 referents before and at the end of an 11-day work period. Personal air sampling was carried out on the two consecutive days before follow-up. Results The TCW’s geometric mean exposure to particulate matter and α-quartz were 604 and 74 µg/m 3 , respectively. The arithmetic mean concentration of elemental carbon was 51 µg/m 3 . The arithmetic mean concentration of SP-D was reduced by 7.6 µg/L in the TCWs and 0.6 µg/L in the referents ( p = 0.04) at the end as compared to before the work period. Subjects who had ever been TCW had lower arithmetic mean CC-16 concentrations at baseline (5.4 µg/L) than subjects who had never worked as TCW (6.4 µg/L). Years worked as TCW was significantly associated with an annual mean decline of the CC-16 concentration of 0.04 µg/L. The concentrations of the biomarker of systemic inflammation, CRP, were not affected by exposure in the TCWs. Current smoking and body mass index have a large impact on the measured biomarker concentrations. Conclusions The results suggest that former and current TCWs have lower serum CC-16 concentrations than referents, while the concentrations of SP-D decreased during exposure. The serum biomarker of systemic inflammation, CRP, was not altered during exposure. Current smoking and BMI were related to the concentrations of all measured biomarkers.